JOINT COMMISSION INTERNATIONAL (JCI) IN THE PEDIATRIC INTENSIVE CARE UNIT (PICU): PREVENTING MEDICATION INCIDENTS THROUGH REMOTE CONTROL. Issue 1 (14th December 2015) - Lazaryan, Moran; Berkovitch, Sofia; Toledano, Michal; Yehoshua, Noa Rosenfeld-; Abu-Kishk, Ibraim; Berkovitch, Matitiahu
Abstract : Introduction: Many medical centers worldwide try to get JCI accreditation in order to improve safety and quality of patient care. Review of medication orders for appropriateness is one of the JCI standards. This process is usually performed by clinical pharmacists joining physician rounds. However, in many medical centers there is a shortage of pharmacists. Objectives: To prospectively investigate the process of remote reviewing of medication orders in the PICU, with a pharmacist located at the pharmacy, without joining physician rounds. To characterize pharmacist recommendations (PR) and decisions taken by the physician. Methods: The study was carried out from 6.3.14–6.10.14 in the PICU (7 beds). Patient demographics, diagnosis and medications prescribed were recorded. Results: 186 review forms were filled in by the pharmacist, regarding 117 admissions(109 children). In 57 (30.6%) forms there was at least one PR. Most common PRs concerned significant interactions (34.5%), dose (26.2%), technical inappropriateness (22.6%) and contraindications (8.3%). Out of all PRs, 51.2% were accepted by the physician, 11.9% rejected and in 36.9% there was no comment. The estimated review time for one medical record was 8.9 min (95% CI, 6.9–10.9), as every additional medication prescribed increased the total review time by 0.8 min (95% CI, 0.49–1.11). Using Monte-Carlo simulation, 108.42 min per day were needed to review all medical records in 95% of the cases. Conclusions: Hospitals facing budget shortages can perform a daily remote review of several departments by an experienced pharmacist instead of participation in physician rounds, and still have a considerable effect on patient safety.